Comparative Study of Intestinal Microbiota Composition of Six Edible Fish Species - Ofek, Tamir; Lalzar, Maya; Laviad-Shitrit, Sivan; Izhaki, Ido; Halpern, Malka (Frontiers in Microbiology, 2021)
Intensive freshwater aquaculture in the Spring Valley, Israel, is implemented mainly in earthen fishponds and reservoirs that are stocked with a variety of edible fish species. Here we sampled six different healthy fish species from these intensive aquacultures. The fish were hybrid striped bass, European bass, red drum (all carnivores), hybrid tilapia, flathead grey mullet (both herbivores) and common carp (an omnivore). Significant differences were found among the intestinal microbiota of the six studied fish species. The microbiota composition diversity was strongly related to the trophic level of the fish, such that there was a significant difference between the carnivore and the herbivore species, while the omnivore species was not significantly different from either group. The most abundant genus in the majority of the fishes’ intestinal microbiota was Cetobacterium. Furthermore, we found that beside Cetobacterium, a specific combination of genera with an abundance of over 10% of the intestine microbiota characterized each fish species. unclassified Mycoplasmataceae, Aeromona and Vibrio (hybrid striped bass); Turicibacter and Clostriciaceae_1 (European bass); Vibrio (red drum); ZOR0006 - Firmicutes (hybrid tilapia); unclassified. Mycoplasmataceae and unclassified Vibrionaceae (grey mullet); and Aeromonas (common carp). We conclude that each fish species has a specific bacterial genera combination that characterizes it. Moreover, diet and the trophic level of the fish has a major influence on the gut microbiota of healthy fish that grow in intensive freshwater aquaculture.